AIDS related eye disease in Burundi, Africa. Issue 3 (1st March 1999) - Cochereau, Isabelle; Mlika-Cabanne, Najoua; Godinaud, Philippe; Niyongabo, Théodore; Poste, Bernard; Ngayiragije, Athanase; Dazza, Marie-Christine; Aubry, Pierre; Larouzé, Bernard
Abstract : AIMS: To determine the prevalence of ocular manifestations in AIDS patients hospitalised in Bujumbura, Burundi, according to their CD4+ lymphocyte count, serological status for CMV and VZV, and general health status. METHODS: Prospective study of 154 consecutive patients who underwent general and ophthalmological examinations, including dilated fundus examination. AIDS was diagnosed on the basis of Bangui criteria and HIV-1 seropositivity. CD4+ lymphocyte counts were determined by the Capcellia method. CMV and VZV antibodies were detected with ELISA methods. RESULTS: The mean age was 37 (SD 9) years and 65% of the patients were male. Active tuberculosis was the most frequent underlying disease (61%). Almost all the patients (99%) were seropositive for CMV and VZV. Among the 115 patients for whom CD4+ lymphocyte counts were available, 86 (75%) had more than 100 cells ×10 6 /l. Ocular involvement comprised 16 cases of microangiopathy, six of opalescence of the anterior chamber, five of retinal perivasculitis, two of zoster ophthalmicus, two of viral retinitis, and one of opalescence of the vitreous. CONCLUSION: In Africa, the prevalence of ocular involvement in HIV infection is far lower than in Europe and the United States, possibly because most African patients die before ocular opportunistic infections occur.